Sensitive subjects : the political aesthetics of contemporary German and Austrian cinema - Mukhida, Leila (Film Europa, 2021)
"Both politically and aesthetically, the contemporary German and Austrian film landscape is a far cry from the early days of the medium, when critics like Siegfried Kracauer produced foundational works of film theory amid the tumult of the early twentieth century. Yet, as Leila Mukhida demonstrates in this innovative study, the writings of figures like Kracauer and Walter Benjamin in fact remain an undervalued tool for understanding cinematic production today. Through illuminating explorations of Haneke, Dresen, and other filmmakers of the post-reunification era, Mukhida develops an analysis centered on the experiences of cinema spectators, showing how medium-specific devices like lighting, sound, and mise-en-scène can help to cultivate political sensitivity"--